Hygrothermal Performance of TES Energy Façade at two European residential building demonstrations – Comparison between Field Measurements and Simulations - Capener, C.; Burke, S.; Le Roux, S., Ott, S. (2019)
In this study, the retrofitted facades of two European multi-unit residential buildings built in the 1950’s and 1980’s are investigated. The demonstration buildings, situated in Munich, Germany and Oulu, Finland, are part of the EU FP7 project E2ReBuild, a European collaboration project, researching and demonstrating industrialised energy efficient retrofitting of residential buildings in cold climates. The demonstration project in Munich, Germany, consisted of two blocks of residential multi-storey buildings in the suburb of Sendling, built in 1954. The buildings were typical examples of the concrete brick constructions, built throughout Germany in the post-war era. The pilot building in Oulu, northern Finland is one of five student apartment buildings in a housing corporation. The building was completed in 1985 according to a Finnish industrialized building system developed in the late 1960's using prefabricated concrete elements for residential buildings, called the "BES system". To improve their energy performance, the retrofit included a façade refurbishment with the TES method utilizing timber based, prefabricated façade elements for the renewal of the building envelope and improved thermal insulation. As part of an advanced monitoring programme, hygrothermal gauges were installed in the walls and they have been monitored for more than one year after the retrofitting. This paper presents the results from the in-situ measurements of the two demonstrations and compares the findings to calculated transient hygrothermal 2D-simulations of the facades utilising the monitored data from the sites in Finland and Germany.